Training in Tolerance – Learning to Self-Regulate Emotions - Rodríguez Ortiz, Angélica María (2019)
Citizenship education has been a significant philosophical concern throughout time. It has also, essentially, been absent from Colombia´ for the past few decades. It is adamant to think about educational processes that will favor this aspect. Conflict in the school merely reflects a violent society, even after Colombia´s peace agreement that led to a period of peace. Teachers should be obligated to teach their students about citizenship so that they may consider themselves agents of social change and become a conscious part of this  transformative effort. This article shows the results of didactic research in the field of philosophy with the objective of identifying the role of self-regulation of emotions when teaching tolerance, based on one´s acknowledgement of the other as a part of a collective whole that serves as the basis for society. In this manner, changes in society can occur as well as opportunities for discussion where aspects such as bullying may be addressed. Action research was the methodology used for this study. Educating citizens implies not only understanding theories and concepts, but also, executing actions that display them. The didactic design for intervention in the classroom was conducted according to the Philosophy for Children strategy or enquire-based learning to foster opportunities for discussion.